Does CSR image matter to hypermarket’s consumers in Malaysia? perspective from persuasion knowledge model - Hong, Kay Tze; Ng, Siew Imm; Ho, Jo Ann; Tan, Houng Chien; LIM, Chui Seong (Universiti Putra Malaysia, 2021)
It is commonly accepted that positive corporate social responsibility (CSR) image brings desirable outcomes, for instance, brand loyalty, improved brand image, enhanced store image, as well as increased visit intention; suggesting there are various direct outcomes of CSR image. Underpinned by the Persuasion Knowledge Model (PKM), this paper proposes that these outcomes are presented in a sequential manner, where there is a core mechanism that relates CSR image to store image and brand awareness, and in turn associate with consumers’ visit intention. A quantitative research methodology has been used where a structured questionnaire was distributed to consumers in selected states in Malaysia using the mall intercept method. Structural equation modelling was applied to examine the proposed model. The discoveries of the current study offer the observed evidence for the correlation between perceived CSR image and hypermarket visit intention, mediated by overall store image and brand awareness. The study emphasises a prominent role of CSR schemes, bringing together the overall hypermarket store image and the hypermarket brand awareness, which will enable hypermarket management to further boost visit intention from consumers.